Jokowi’s “Look West” foreign policy : expanding Indonesia’s sphere of influence? - Sebastian, Leonard C. (2015)
While President Jokowi has to contend with intense short-term domestic challenges, it does not mean he will completely decry the internationalist foreign policy outlook of Susilo Bambang Yudhoyono. His primary strategies will be to turn Indonesia into a “global maritime nexus” and pursue a “Look West” strategy.